2004
DOI: 10.1348/014466504323088051
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cognitive changes: Psychometric properties of six cognitive tests

Abstract: The psychometric properties of the GNT and Silhouettes Test indicated that they are useful tools for monitoring even small cognitive changes. In contrast, the verbal fluency tests and the new Symbol Digit Test are only suitable for monitoring large changes in performance. The Modified Card Sorting Test is an unreliable tool for monitoring 'executive' functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 38 publications
6
63
1
1
Order By: Relevance
“…This practice effect has been documented in previous research using the aforementioned tests [Fitts, 1954;Wexler et al, 1998;Fastenau et al, 2001;Bird et al, 2004;Hinton-Bayre and Geffen, 2005;Miller et al, 2009;Solana et al, 2010]. These tests are associated with the prefrontal cortex [Shibuya-Tayoshi et al, 2007], precentral gyrus, cingulate gyrus, medial frontal gyrus [Zakzanis et al, 2005], left middle frontal gyrus, and posterior parietal cortex [Usui et al, 2009].…”
Section: Discussionsupporting
confidence: 71%
“…This practice effect has been documented in previous research using the aforementioned tests [Fitts, 1954;Wexler et al, 1998;Fastenau et al, 2001;Bird et al, 2004;Hinton-Bayre and Geffen, 2005;Miller et al, 2009;Solana et al, 2010]. These tests are associated with the prefrontal cortex [Shibuya-Tayoshi et al, 2007], precentral gyrus, cingulate gyrus, medial frontal gyrus [Zakzanis et al, 2005], left middle frontal gyrus, and posterior parietal cortex [Usui et al, 2009].…”
Section: Discussionsupporting
confidence: 71%
“…In their research, they used the classic Kety-Schmidt technique for the quantitative measurement of whole brain blood flow and metabolism (27), before, during, and after the performance of a challenging cognitive task [the Wisconsin Card Sorting Test (28)(29)(30), which exhibits a significant learning component (31)(32)(33)]. During task performance, they observed an increase in whole brain blood flow, glucose consumption, and lactate production, but no increase in oxygen consumption.…”
mentioning
confidence: 99%
“…However, Plumet, Gil, & Gaonac'h, (2005) found that education no longer had an effect on distractive errors after age 70, and attentional focus on sorting rules were more affected by age than education. Total number of errors on the M-WCST (Bird, Papadopoulou, Ricciardelli, Rossor, & Cipolotti, 2004), number of categories completed (Bird et al, 2004;Obonsawin et al, 1999), number and percent of perseverative errors (Obonsawin et al, 1999) have been significantly associated with IQ. Lineweaver et al (1999) found that sex is associated with non-perseverative errors, such that men make more of these errors than women, but generally there are no sex differences for the M-WCST (Caffarra, Vezzadini, Dieci, Zonato, & Venneri, 2010;Obonsawin et al, 1999).…”
Section: Introductionmentioning
confidence: 93%